Efeitos da deriva de clomazone, aplicado isoladamente ou em mistura com ametryn, sobre características produtivas de laranjeira 'Hamlin' - Timossi, P.c. [UNESP] (2001)
This experiment aimed to evaluate the effect of increasing clomazone (sprayed alone or in mixture with ametryn) drift simulation on quantitative and qualitative aspects of orange production when applied at two developmental plant stages: flowering and initial fruit development (fruits 2 cm diameter or smaller). Increasing drifts of clomazone, in two formulations, and clomazone in mixtures with ametryn were tested. Fruit morphological features, fruit color, flower and fruit abortion and leaf chlorophyll content were evaluated. Simulated drift similar to the recommended dose of clomazone and clomazone plus ametryn caused fruit abortion in citrus at the stage of fruits 2 cm diameter or smaller. Lower drift doses did not result in fruit abortion. Fruit diameter reduction was observed with drift off above 25% of clomazone alone recommended rate and 50% when in mixture with ametryn or in microcapsule formulation. Clomazone drift at 50% of the recommended rate (alone or in mixture with ametryn ) caused clorotic and necrotic spots in the fruit peel. Drift did not affect juice quality in any of the treatments tested.